Vertical section construction of wells at Kuyumbinsky oil field via percussive-rotary drilling with DTH hammer; IOP Conference Series: Earth and Environmental Science; Vol. 43 : Problems of Geology and Subsurface Development - Buzanov K. V. Kirill Vladimirovich (Latest Technologies in Oil and Gas Driling, 2016)
Title screen